2015
DOI: 10.1292/jvms.15-0167
|View full text |Cite
|
Sign up to set email alerts
|

Coincidental detection of genomes of porcine parvoviruses and porcine circovirus type 2 infecting pigs in Japan

Abstract: The infection status of 15 viruses in 120 pigs aged about 6 months was investigated based on tonsil specimens collected from a slaughterhouse. Only 5 species of porcine parvoviruses and porcine circovirus type 2 (PCV2) were detected at high frequencies; 67% for porcine parvovirus (PPV) (PPV-Kr or -NADL2 as the new abbreviation), 58% for PPV2 (CnP-PARV4), 39% for PPV3 (P-PARV4), 33% for PPV4 (PPV4), 55% for PBo-likeV (PBoV7) and 80% for PCV2. A phylogenetic analysis of PPV3 suggested that Japanese PPV3s showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…PCV2 frequencies reported over last (Sun et al, 2015), while another work, in Japan found 80% of positive tonsil samples collected from pigs aged 6 months (Saekhow et al, 2015). Our results showed that PCV2 was detected in all states, with a frequency of 57% of positive herds, and 49% of positive animals, in five European countries 42% of fecal samples taken from both healthy and diarrheic pigs were positive and the percentage was higher in healthy compared to diseased animals (Zhou et al, 2016), which suggest that most PCV2 infections were subclinical.…”
Section: Resultsmentioning
confidence: 93%
“…PCV2 frequencies reported over last (Sun et al, 2015), while another work, in Japan found 80% of positive tonsil samples collected from pigs aged 6 months (Saekhow et al, 2015). Our results showed that PCV2 was detected in all states, with a frequency of 57% of positive herds, and 49% of positive animals, in five European countries 42% of fecal samples taken from both healthy and diarrheic pigs were positive and the percentage was higher in healthy compared to diseased animals (Zhou et al, 2016), which suggest that most PCV2 infections were subclinical.…”
Section: Resultsmentioning
confidence: 93%
“…In another study conducted in Japan, PPVs were detected in high frequencies as coinfections in PCV2‐infected pigs; PPV1 coinfection was found in 67% of the pigs, PPV2 in 58%, PPV3 in 39%, PPV4 in 33%, and PBoV7 was detected in 55% of the pigs . Overall, the studies show that PPV1 and PPV2 are the most prevalent parvoviruses in pigs . PPV1, PBoV3, and PBoV4 are the only pig‐associated Parvoviridae members that have been cultured in vitro …”
Section: Single‐stranded Dna Viruses In Pigsmentioning
confidence: 83%
“…Parvovirus DNA can be detected, even in healthy pigs, in a wide range of pig tissues including tissues of possible interest for xenotransplantation such as liver and kidney . The PPVs and PBoVs are considered possible triggers for the development of systemic disease in PCV2‐infected pigs . A survey in the United States using random samples submitted for diagnostics from 2006 to 2013 showed the prevalence of PPV in tissues as follows: 15.2% for PPV1, 42.7% for PPV2, 9.1% for PPV3, 4.3% for PPV4, and 3.0% for PPV5 .…”
Section: Single‐stranded Dna Viruses In Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPVs are host‐specific to pigs. Among PPVs, PPV1 causes major reproductive failure in sows characterized by the stillbirth, mummification, embryonic death and infertility (Karniychuk & Nauwynck, ) and is an economically important viral pathogen for pig industry worldwide (Zhou & Yang, ), while other PPVs are usually co‐infected with other pathogens, and may play associated role in disease development (Ghosh et al, ; Saekhow et al, ). Recently, a number of novel PPVs, such as PPV5, PPV6 and PPV7, have been discovered using advanced molecular and biological techniques (Palinski, ; Schirtzinger, Suddith, Hause, & Hesse, ; Xiao, Halbur, & Opriessnig, ).…”
Section: Resultsmentioning
confidence: 99%